Analysis of Global Connections. Countries Closer and Further in Development in Globalization - Monika HADAS-DYDUCH (Communications of International Proceedings, 2020)
Globalization currently affects every person and every sphere of his life. For this reason, we have financial, social, cultural, political, ecological, economic and even globalization, as shown by recent global events related to COVID19, perhaps even globalization of illness. Globalization is not new but is changing fast. Global interaction is centuries old, reflecting a human instinct to find new opportunities, discover new people and places, and exchange ideas and goods. The article deals with the topic of general globalization, combining Economic Globalization, Social Globalization, and Political Globalization. The study was based on data provided by the Swiss Economic Institute. The aim of the article is to familiarize readers with this phenomenon, analysis of the development trend of general globalization and analysis of similarities in development with other countries. The aim of the article is to familiarize readers with the phenomenon of globalization, presentation of the genesis of globalization and detailed characteristics of individual types of globalization. Moreover, the aim of the study is to analyze the development tendency of general globalization and to analyze similarities in development with other countries. The article classifies countries into groups that are most similar to each other in terms of the development of globalization. Grouping was made according to different types of globalization. The aim of the article is to analyze globalization in the context of the intensity of this phenomenon in individual countries.
Keywords: Globalization; Integration; Political Globalization; Wavelets.